Minimally Invasive Correction of Prolapsed, Gangrenous Distal Limb of Loop Ileostomy to End-Loop Stoma - John Shelton; Sittampalam Rajendra (Case Reports in Surgery)
Introduction. Prolapse can be a complication of loop stomas. A prolapsed stoma which cannot be reduced or complicated with strangulation needs surgical correction. This case report describes a minimal access correction of a prolapsed gangrenous distal limb of ileostomy. Presentation of Case. A 67-year-old male patient was diagnosed with a lower rectal carcinoma, staged T3N1M0. Following neoadjuvant chemoradiation, he underwent a laparoscopic anterior resection with a defunctioning loop ileostomy. One month later, he presented with prolapse of the distal limb of the ileostomy. The limb was gangrenous and the gangrenous part was removed by using a linear GI stapler, and the loop ileostomy was converted to end-loop ileostomy. Discussion. It is a simple and technically feasible method for treating a prolapsed loop of the stoma. It is less invasive and has minimal postoperative complications. This technique reduces the duration of the hospital stay of the patient. Conclusion. Stapled assisted correction of prolapsed stoma avoids unnecessary laparotomy and aids in expedite recovery after surgery. It is beneficial for a surgeon to be familiar with the minimal access correction for stoma prolapse.